The Role of Sharia Fintech in Developing Islamic Economy In The Digital Era In Indonesia - Hehanussa, Umi Kalsum; Syarifuddin, Syarifuddin (Islamic Economics, Finance, and Banking Review, 2021)
Indonesia is one of the countries that has great potential for the development of the digital economy. The development of financial technology in Indonesia is increasing rapidly lately. This can be seen from the large response of indonesian people to the existence of fintech. This research aims to find out how sharia fintech plays in developing the Islamic economy in the digital age in Indonesia. This research method uses literature review approach by using the study materials of previous journals, books and other references. The results showed that FinTech plays an active role in the development of the national sharia economy in the digital era in Indonesia, as well as the strengthening of startup companies that can strengthen the halal industry chain, so as to create a sharia economy based on technology infrastructure. With this Islamic FinTech is expected in the future can improve inclusive finance, and can increase the economic growth of Islam in Indonesia. Fintech is an alternative solution to the creation of sharia financial transactions that are easier, faster and more efficient. In addition, sooner or later with the potential and wealth of Natural Resources Indonesia has the opportunity to become the center of the world halal industry that will promote halal food, halal fashion and halal tourism to go to the Global Islamic Economy.